Utilization of Youtube Media in Improving Students' Language Skills - Nyak mauliza Warzukni; Nina Rahayu; Yustizar Yustizar (At-Tarbawi: Jurnal Pendidikan, Sosial dan Kebudayaan, 2023)
This study aims to describe the improvement of students' speaking activities and skills through the use of YouTube media. On the material of fiction stories. The type of research used is class action research. Conducted in two cycles, the stages are: planning, action implementation, observation and reflection. The subjects of this study were fourth grade students of MIN 2 Langsa. Data collection techniques through: tests, observation sheets of student activity, and teacher activity. The results of the first cycle research obtained teacher performance scores reached (75.00%) and the second cycle increased to (100%). The results of the student speaking skills test in cycle I who reached the KKM score were 14 students and those who did not reach the KKM were 5 students with an average class score of (73.69%). And in the implementation of the second cycle test, 18 students completed and only one student did not complete with the class average value increasing to (94.73%). From this discussion it can be concluded that there is an increase in the speaking skills of fourth grade students of MIN 2 Langsa with the utilization of YouTube media